EFFECT OF BILINGUALISM ON COGNITIVE FLEXIBILITY: A PSYCHOLINGUISTIC ANALYSIS - Sakharova , Olga; Nedashkivska , Tetiana; Kozak , Svitlana; Nikolaieva , Tetiana; Romanchuk , Svitlana (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
Bilingualism is a factor that activates the development of executive functions and contributes to cognitive flexibility. However, scientific research has little to do with the psychocognitive aspects of cognitive flexibility. It overlooks the emotional component of this phenomenon, as most cognitive science and psychology research have historically prioritized quantifiable and behaviorally observable elements of cognition. Thus, this research focuses on examining the influence of bilingualism on cognitive flexibility and components of social cognition in students through an experimental study. As for the research design, a Quasi-Experimental Study with intergroup comparison was chosen. This study employed a between-groups quasi-experimental design to compare the cognitive flexibility of bilingual and monolingual students, while addressing the ethical limitations of manipulating natural variables, such as language background. The results: The sample consisted of 40 participants (20 bilinguals and 20 monolinguals), matched for age (p = 0.87) and gender. Education years differed (16.48 vs 14.95, p < 0.001). Bilinguals outperformed monolinguals in D2 attention (1049.76 vs. 865.21, p = 0.001), RL/RI-16 memory (14.68 vs. 13.30, p = 0.027), and emotional fluency (19.00 vs. 14.87, p = 0.011). Cognitive flexibility was higher in bilinguals (84.5 vs 78.2, p = 0.03). Age–flexibility correlation was nonsignificant (r = 0.051, p = 0.351). Thus, it can be assumed that bilingualism contributes to the development of cognitive flexibility and emotional awareness, as this phenomenon holds promise for speech therapy and psycholinguistic practice.JEL Classification Codes: K00, K11, K12, K33.